2018
DOI: 10.1038/s41598-018-35017-y
|View full text |Cite
|
Sign up to set email alerts
|

Retinal micro-vascular and aortic macro-vascular changes in postmenopausal women with primary hyperparathyroidism

Abstract: Aim of the study was to evaluate the micro and macro-vascular changes in patients with primary hyperparathyroidism (PHPT) compared to controls. 30 postmenopausal PHPT women (15 hypertensive and 15 normotensive) and 30 normotensive controls underwent biochemical evaluation of mineral metabolism and measurements of arterial stiffness by 24 hour ambulatory blood pressure monitoring. Retinal microcirculation was imaged by a Retinal Vessel Analyzer. PHPT patients also underwent bone mineral density measurements and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, there was a positive correlation between daily proteinuria and PTH levels in patients with diabetic nephropathy 29 . Compared with the normal control group, postmenopausal women with primary hyperparathyroidism have retinal microvascular stenosis 30 , which might lead to retinal ischemia and further retinopathy. On the contrary, a study by Hekimsoy et al 31 .…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, there was a positive correlation between daily proteinuria and PTH levels in patients with diabetic nephropathy 29 . Compared with the normal control group, postmenopausal women with primary hyperparathyroidism have retinal microvascular stenosis 30 , which might lead to retinal ischemia and further retinopathy. On the contrary, a study by Hekimsoy et al 31 .…”
Section: Discussionmentioning
confidence: 96%
“…Patel et al reported that participants with excessive calcium intakes above the median had lower serum PTH concentrations [ 69 ]. In a previous study, low serum PTH levels were suggested to be associated with retinal vascular diameters and a decreased risk of retinal microvascular impairment [ 70 ]. Pathogenesis of ARMD has proposed that retinal vascular diameters was associated with the severity of ARMD [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…PTH associated with stiffness? Calcium ✓ (178,185) X, (179) ✓ (180) X, (179) ✓ (180) X (171) Conflicting data; Danish RCT negative but subgroup with highest calcium improved Left ventricular mass PTH à cardiac myocyte hypertrophy?…”
Section: Vascular Stiffness Flow Mediated Dilationmentioning
confidence: 99%
“…Despite the abundance of observational studies establishing an increased prevalence of abnormalities in surrogate markers of CV outcomes in patients with PHPT (Table 3), ( 73,169‐173,175,178‐180,183‐185,187‐190,192,195,196 ) little evidence exists on causality as could be inferred from reversibility post‐PTX (Table 4). ( 74,170,171,195 )…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation